Cognitive Factors Associated with Nurses' Successful Detection of Sepsis Versus Failure to Rescue. Issue 1 (June 2013) - Doig, Alexa; Baraki, Katie; Drews, Frank
The objective of this study was to identify cognitive predictors of failure to rescue among acute care oncology nurses. Fifty-seven oncology nurses were video recorded as they monitored a patient developing a life threatening non-routine event in a high fidelity acute care hospital setting, in the case of this analysis– sepsis. Nurses who had higher levels of level 1 situation awareness (i.e., use limited data from the electronic health record and assessment findings) were more likely to detect sepsis and initiate an appropriate response. In the failure to rescue cases, the majority of errors occurred at the level of perception or level 1 situation awareness. Twenty percent of nurses who identified that the patient was septic, were not able to project the potential severity of the situation and apply appropriate interventions.